Alternative splicing signature of alveolar type II epithelial cells of Tibetan pigs under hypoxia-induced - Yuan, Haonan; Liu, Xuanbo; Wang, Zhengwen; Ren, Yue; Li, Yongqing; Gao, Caixia; Jiao, Ting; Cai, Yuan; Yang, Yanan; Zhao, Shengguo (Frontiers in Veterinary Science, 2022)
Alternative splicing (AS) allows the generation of multiple transcript variants from a single gene and affects biological processes by generating protein diversity in organisms. In total, 41,642 AS events corresponding to 9,924 genes were identified, and SE is the most abundant alternatively spliced type. The analysis of functional categories demonstrates that alternatively spliced differentially expressed genes (DEGs) were enriched in the MAPK signaling pathway and hypoxia-inducible factor 1 (HIF-1) signaling pathway. Proteoglycans in cancer between the normoxic (21% O2, TN and LN) and hypoxic (2% O2, TL and LL) groups, such as SLC2A1, HK1, HK2, ENO3, and PFKFB3, have the potential to rapidly proliferate alveolar type II epithelial (ATII) cells by increasing the intracellular levels of glucose and quickly divert to anabolic pathways by glycolysis intermediates under hypoxia. ACADL, EHHADH, and CPT1A undergo one or two AS types with different frequencies in ATII cells between TN and TL groups (excluding alternatively spliced DEGs shared between normoxic and hypoxic groups), and a constant supply of lipids might be obtained either from the circulation or de novo synthesis for better growth of ATII cells under hypoxia condition. MCM7 and MCM3 undergo different AS types between LN and LL groups (excluding alternatively spliced DEGs shared between normoxic and hypoxic groups), which may bind to the amino-terminal PER-SIM-ARNT domain and the carboxyl terminus of HIF-1α to maintain their stability. Overall, AS and expression levels of candidate mRNAs between Tibetan pigs and Landrace pigs revealed by RNA-seq suggest their potential involvement in the ATII cells grown under hypoxia conditions.